Empowerment of Women in District Baramulla of Jammu and Kashmir through Self-Help Groups (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
In India, more emphasis is on sustainable development and women’s empowerment, necessitating microcredit. Empowering women in social, political, economic, and legal dimensions became vital to transform an idle society into a self-sufficient community. Self-Help Groups are seen as one of the most effective ways to bring women to the forefront of society. Credit is required for various purposes due to the development of SHGs (domestic, health, festivals, repayment of old debts, investment, etc.). After joining the SHG, members engage in various economic activities (product collecting, processing, and selling, individual business, dairy, and so on). SHG members profit from savings habits, financial independence, self-confidence, social cohesion, asset ownership, debt freedom, extra jobs, etc. The present study investigates the role of self-help groups in women’s economic, social, and political empowerment and provides policy recommendations for preserving women’s empowerment through self-help groups